Does an increase in estimated pulse wave velocity increase the incidence of hypertension?. Issue 12 (12th December 2021) - Chen, Haojia; Wu, Weiqiang; Fang, Wei; Chen, Zhichao; Yan, Xiuzhu; Chen, Youren; Wu, Shouling
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: As a risk indicator of hypertension, arterial stiffness is difficult to measure. Thus, we aimed to evaluate the association between estimated pulse wave velocity (ePWV) as a convenient indicator and the incidence of hypertension. Methods: The Kailuan cohort was selected for statistical analysis and 54 849 individuals were included in the final cohort. Multiple linear regression was used to analyse the correlation between ePWV and mean SBP (SBP_m) measured at five time points over a 10-year period and between ePWV and mean DBP (DBP_m) measured at five time points over a 10-year period. Logistic regression was used to analyse the effect of estimated arterial stiffness on hypertension. Results: The mean age of individuals was 48.44 ± 9.32 years, and 41 419 individuals (75.51%) were male. A multiple linear regression analysis showed that ePWV was positively correlated with both SBP_m and DBP_m. For every 1 cm/s increase in ePWV, SBP_m and DBP_m increased by 5.60 and 2.12 mmHg, respectively. A logistic regression analysis showed that in the total cohort, the incidence of hypertension in populations with moderate, moderate–high and high ePWV values was 3.03, 5.44 and 7.87-times higher, respectively, compared with individuals with low ePWV values. ePWV had a higher predictive value in female and middle age population compared with male and the eldly population grouped by sex and age respectively. Conclusion: ePWV positively correlates with both SBP_m and DBP_m, and an increase in ePWV is associated with an increase in the incidence of hypertension.